A Voice in the Wind - Rivers, Francine 1947- (Wheaton, Ill. : Tyndale House, 1993)
A young Christian slave girl struggles to reconcile her love for a handsome aristocrat with her deep faith, as she confronts the dark and decadent forces of imperial Rome.